Pengaruh Warm Bath Dengan Aromaterapi Sandalwood Terhadap Peningkatan Kualitas Tidur Pada Lanjut Usia - WIDIARTI, Widiarti; , Umi Budi Rahayu, S.Fis, M.Kes; , Totok Budi Santoso , S.Fis , MPH (2015)
Background: Quality sleep is someone to his satisfaction, so it does not show feelings of fatigue, anxiety, lethargy, apathy, blackish around the eyelids, red conjunctiva, eye irritation, fragmented attention, dizziness and frequent yawning or sleepy. Elderly has decreased in many body system, including the impact on sleep disorders. Sleep disoeders can affaect the quality of life. Therapeutic feet soak in warm bath ini the blood vessels and improve microcirculation vasodilatation theraby increasing the quality of sleep. Objective: This study aimed to determine the effect of a warm bath with aromatherapy sandalwood in improving sleep quality in elderly. Methods: This study is a quasi experiment research design Design Pre and Post test control group design. Population 66 elderly sleep disturbance over 60-90 years old, a sample of 15 respondents. Sampling using purposive sampling, testing the effect of Paired sample t-test and analysis of data with statistical tests uji Shampiro wilk test with significance level α = 0.05. Sleep quality scores measured by the Pittsburgh Sleep Quality Index Results: indicates that the warm bath with aromatherapy sandalwood effectively used to improve sleep quality in older adults who experience sleep disturbances Conclusion: With these results we can conclude there is the influence of the warm bath with aromatherapy sandalwood to improving the quality of sleep of elderly. Hopefully this research can continue and can be useful for researchers, medical personnel or the general public.